2018
DOI: 10.3389/fnins.2018.00622
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Astrocytic HMGB1 Signaling in Amyotrophic Lateral Sclerosis

Abstract: Astrocytes have emerged as critical elements for the maintenance and function of the central nervous system. The expression on their cell membrane of RAGE and TLR4 receptors makes astrocytes susceptible to High-mobility group box 1 (HMGB1), a nuclear protein typically released in the extracellular milieu by living cells experiencing physiological stress conditions or by damaged cells. Here, we show that the interaction of HMGB1 with normal spinal cord astrocytes induces the astrocytic production of neurotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…In murine models of ALS, it was initially noted that preventing NF-kB activation in astrocytes did not ameliorate the pathological phenotype [173,174] or it was even detrimental [175]. In line with these observations, we demonstrated that activating NF-kB in astrocytes can lead to the production of growth factors that are known to support neuronal survival, namely brain-derived neurotrophic factor (BDNF) and GDNF [176]. However, pharmacological treatment with the NF-kB inhibitor Withaferin A ameliorated the phenotype of several models of ALS [177][178][179].…”
Section: Shared Pathways Of Astrocyte Dysfunction In Neurodegenerative Diseasessupporting
confidence: 69%
“…In murine models of ALS, it was initially noted that preventing NF-kB activation in astrocytes did not ameliorate the pathological phenotype [173,174] or it was even detrimental [175]. In line with these observations, we demonstrated that activating NF-kB in astrocytes can lead to the production of growth factors that are known to support neuronal survival, namely brain-derived neurotrophic factor (BDNF) and GDNF [176]. However, pharmacological treatment with the NF-kB inhibitor Withaferin A ameliorated the phenotype of several models of ALS [177][178][179].…”
Section: Shared Pathways Of Astrocyte Dysfunction In Neurodegenerative Diseasessupporting
confidence: 69%
“…Our results indicate therefore that HMGB1 activation of TLR2, TLR4 and RAGE in SOD1 G93A mice may be compensated for by other endogenous ligands, which may explain the lack of efficacy on survival with anti-HMGB1 antibody treatment. Furthermore, others have also suggested that astrocytic HMGB1 signalling in ALS could be neuroprotective via release of neurotrophic factors such as brain-derived neurotrophic factor and glial cell line-derived neurotrophic factor [48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HMGB1 possess two DNA-binding terminals (termed A and B-boxes) and a negatively charged C-terminal tail that contains a recurring chain of 30 glutamic and aspartic acids ( Aucott et al, 2018 ; Paudel et al, 2019a ). In recent days, HMGB1 has been extensively explored in several HMGB1 mediated neurological pathologies including Epileptogenesis ( Maroso et al, 2010 ; Paudel et al, 2019b ), Parkinson’s disease (PD) ( Gao et al, 2011 ; Angelopoulou et al, 2018 ), Alzheimer’s disease (AD) ( Takata et al, 2004 ; Paudel et al, 2020a ), Multiple sclerosis (MS) ( Andersson et al, 2008 ; Paudel et al, 2019a ) and ALS ( Brambilla et al, 2018 ; Paudel et al, 2020c ) and Brain injuries ( Okuma et al, 2012 ; Paudel et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%